2018
DOI: 10.4314/ahs.v18i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Child sexual abuse and disclosure in South Western Nigeria: a community based study

Abstract: IntroductionThe true burden of child sexual abuse in Nigeria is not known as most reports are institutional based. This study was designed to determine population level data on the burden and pattern of child sexual abuse among adolescents in South Western Nigeria.MethodsA community based study among adolescents in SouthWestern Nigeria. Semi- structured interviewer administered questionnaire was used to collect data from respondents selected through a multistage sampling technique. Analysis was with SPSS versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
44
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 15 publications
18
44
1
7
Order By: Relevance
“…Majority of studies in Africa have shown friend and neighbours to be the most common perpetrators while relatives were most cited in Asian studies. This observation is supported by a number of other authors that CSA is usually perpetrated by someone known to the child (David et al, 2018). Finally, CSA can take place in a variety of setting, at home, school, open place, in the public event and neighborhood.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Majority of studies in Africa have shown friend and neighbours to be the most common perpetrators while relatives were most cited in Asian studies. This observation is supported by a number of other authors that CSA is usually perpetrated by someone known to the child (David et al, 2018). Finally, CSA can take place in a variety of setting, at home, school, open place, in the public event and neighborhood.…”
Section: Discussionsupporting
confidence: 66%
“…Finally, CSA can take place in a variety of setting, at home, school, open place, in the public event and neighborhood. Majority of studies across the world have found similar pattern (David et al, 2018;Lalor, 2004). This shows children are vulnerable everywhere hence coordinated approach is crucial in addressing CSA.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A violência sexual infanto-juvenil pode se expressar de diferentes formas e conceitos. O abuso sexual é um tipo de violência que envolve atos ou jogos sexuais praticados por qualquer pessoa contra a criança ou adolescente, por meio de suborno, violência física ou ameaça, almejando o prazer sexual do agressor, podendo ocorrer com ou sem contato físico (2,5).…”
Section: Introductionunclassified
“…They found a 25% prevalence among adolescents studied. Most perpetrators were boyfriends or neighbours, and only a third of the cases reported the abuse 1…”
mentioning
confidence: 99%